Effect of Information and Communication Technology (ICT) on Students’ Achievement in Christian Religious Knowledge in Secondary Schools: A Case Study of Ihiala Local Government Area (LGA) in Nigeria - Ethel Ezeh, Mary-Noelle (African Journal of Education,Science and Technology (AJEST), 2013)
This study investigated the effect of ICT topic-focused software programme on students‟ achievement in Christian Religious Knowledge in Secondary Schools in Ihiala Local Government Area (LGA), Anambra State, Nigeria. Purposive stratified sampling was used to draw 120 SS I & II students from two single-sex schools in Ihiala LGA to participate in the study. Two research questions and two hypotheses guided the study. The instrument, Achievement Test in Christian Religious Knowledge (ATCRK), was used in the study. The instrument was validated and a reliability co-efficient of 0.072 was obtained using spilt-half method of Pearson‟s Product Moment formula. This was considered high enough for the study. Mean and standard deviations were used for answering the research questions. The hypothesis were tested using the t-test statistics at P < 0.05 level of significance. The results of the findings showed that students who were taught using ICT topic-focused software programme achieved better scores than those taught using the traditional instructional material. The results also showed that female students‟ performed better than their male counterparts when they were taught Christian Religious Knowledge with topic-focused software programme. Based on the findings of this study, it was recommended that the use of ICT tools in teaching and learning Christian Religious Knowledge be made imperative in all Secondary Schools. Curriculum planners should also try to include the use of more interactive ICT curriculum-specific application in teaching and learning Christian Religious Knowledge. Software developers should be trained and encouraged to develop nationally usable e-education software in teaching and learning Christian Religious Knowledge. The use of ICT in teaching and learning Christian Religious Knowledge could provide an effective remedy to the unsatisfactory persistent and prolonged situation of poor students‟ achievements in the subject.